LINGUISTIC LANDSCAPE OF THE BALTIC STATES: DATA, RESULTS, FUTURE RESEARCH PERSPECTIVES - Lazdiņa, Sanita; Pošeiko, Solvita; Marten, Heiko F. (Via Latgalica, 2013)
This paper gives an overview of activities which have been carried out in the fi eld of Linguistic Landscapes (LL) at Rēzekne University College (Rēzeknes Augstskola, RA) since 2008. Between 2009 and 2012, LL research was carried out within the framework of one of the work groups of the TILRA project funded by the European Social Funds (ESF). TILRA has had the overarching aim to support research in the humanities which may be helpful for understanding local identity and contribute to the regional development of Latgale. In this light, LL research has proven to be of high value for triggering effects in education at all levels, academic research and for enhancing discussions within politics and regional development. The paper fi rst provides a summary of the basic principles of the LL approach as they have been developed in the international linguistic community throughout the past decade. It addresses how the method has gained more and more popularity world-wide and moved from mostly quantitative and descriptive reports of the languages on signs in the public sphere to by far more interdisciplinary studies. Today, scholars in the fi eld of LL do research on signs of all kinds with regard to aspects such as functions of languages, semiotics, or the negotiation of and confl icts on ownership of and power in a territory. After this general introduction, the paper reports of how the LL method has been taken to the Baltic States, at fi rst in education and research at RA. The first of these activities were limited to Latvia (Rēzekne, Ventspils), but soon research was also taken to Lithuania (Alytus, Druskininkai) and Estonia (Pärnu, Narva). The paper then provides examples of the results of the research. On the one hand, a data base with almost 5,000 signs from the 6 towns in the Baltic States where research was carried out has been created. This data base allows for a detailed contrastive analysis of signs in the public sphere with regard to aspects such as the number and hierarchies of languages on the signs and their locations and functions. In cases of, for instance, signs at shops, also the type of shop is included. The research found 23 different languages, of which the titular languages of the Baltic States (Estonian, Latvian, Lithuanian) dominated, followed by English and Russian. English appears mostly as a language of high prestige, often with predominantly symbolic value. Other languages were rare, and also the regional language of Latgalian was identified on only a small proportion of the signs in Rēzekne. In total, about one third of the signs in the data base is multilingual, the other two thirds displaying only one language (most often, but not always, the respective titular language). On the other hand, the data base has been supplemented by qualitative data obtained through 46 interviews (conducted in Rēzekne, Narva and Druskininkai) with people working in the field of tourism, but also with passers-by in the streets. The interviews focus on e.g. roles of languages in tourism, reflections of regional identities in the LL or connections between the LL and language policies. With regard to tourism, English was found to be of highest importance as a lingua franca, but also Russian plays an important role. The research also asked explicitly whether small private signs may reflect linguistic or ethnic conflicts, but no such examples were found, and interviews confirmed that on a small, local level, the LL is not a place where such conflicts take place. The paper then reports of impacts which the LL activities have had with regard to the popularization of linguistic topics in society at large. By now, several schools in Latvia have used the LL approach in their activities and adapted it to their individual purposes. Other debates to which the LL research has contributed and where LL research and the publications created during the project have proven to have an impact on broader societal developments, are e.g. the relation between language use in private and in public domains, the functions of different languages in the internet, reflections of paralinguistic notions and the economic potential of languages, the latter in particular with regard to the Latgalian language. Finally, the paper highlights directions of future research. This includes the analysis of language contact in micro situations such as on specific notice boards or the use of LL data in discourse analytical studies. More broadly speaking, it is envisaged also to analyse existing LL patterns in the Baltic States in contrast to LL studies in other parts of the world, e.g. the role of Latgalian in the LL vis-à-vis other regional or minority languages in Europe. The paper also provides an overview of important publications which have been prepared or triggered as a result of the LL research, including several master theses and an on-going PhD project. In total, the paper thereby shows how the TILRA project has contributed to establishing research and awareness of the LL approach in the Baltic States, and how it at the same time has given LL research in the Baltic States a recognized standing among international LL researchers. The paper is supplemented by a list of LL publications, including many of those publications published by the project’s participants both in Latvian and international contexts, and by the questionnaire which served as a point of departure for the semi-structured interviews during the research.